Effectiveness of Ecoenzyme from Eucalyptus Leaves Produced by Umkm Lamongan as A Disinfectant - Abdillah Juang Airlangga Putra (Publikasi Indonesia, 2026)
Hand washing with running water for at least 20 seconds is one of the most effective methods for preventing the transmission of infection-causing microorganisms. However, the increasing use of alcohol-based hand disinfectants as a practical alternative has raised concerns because of adverse effects such as skin irritation, dryness, and dehydration. Consequently, plant-based disinfectants with fewer side effects have attracted growing attention. One potential material is eucalyptus (Melaleuca leucadendra), whose leaves can be fermented into ecoenzyme containing bioactive compounds with reported antibacterial properties. This study aimed to evaluate the antibacterial effectiveness of eucalyptus leaf ecoenzyme produced by Lamongan MSMEs as a hand disinfectant. A simple experimental study with a comparative design was conducted using bacterial swab samples collected from the fingers of three randomly selected Universitas Airlangga students. Antibacterial activity was assessed by comparing bacterial colony counts on Mueller–Hinton agar after treatment with eucalyptus leaf ecoenzyme at concentrations ranging from 10% to 100%. The results showed that none of the tested concentrations significantly reduced bacterial colony counts, indicating limited antibacterial activity against bacteria on the hand surface. It can be concluded that eucalyptus leaf ecoenzyme produced by Lamongan MSMEs at concentrations of 10%–100% does not demonstrate significant antibacterial effectiveness. These findings suggest that optimization of the fermentation process, raw-material composition, and organic-acid content is necessary before the ecoenzyme can be recommended as an alternative organic hand disinfectant.